Singapore Grouper Iridovirus Induces Glucose Metabolism in Infected Cells by Activation of Mammalian Target of Rapamycin Signaling - Guo, Xixi; Zheng, Qi; Pan, Zanbin; Huang, Youhua; Huang, Xiaohong; Qin, Qiwei (Frontiers in Microbiology, 2022)
Singapore grouper iridovirus (SGIV), a member of the Iridoviridae family, is an important marine cultured fish pathogen worldwide. Our previous studies have demonstrated that lipid metabolism was essential for SGIV entry and replication, but the roles of glucose metabolism during SGIV infection still remains largely unknown. In this study, we found that the transcription levels of key enzymes involved in glycolysis were regulated in varying degrees during SGIV infection in grouper spleen (EAGS) cells based on the transcriptomic analysis. Quantitative PCR and western blot analysis also indicated that the expression of both glucose transporters (GLUT1 and GLUT2) and the enzymes of glucose metabolism (hexokinase 2, HK2 and pyruvate dehydrogenase complex, PDHX) were upregulated during SGIV infection in vivo or in vitro, suggesting that glycolysis might be involved in SGIV infection. Exogenous glucose supplementation promoted the expression of viral genes and infectious virion production, while glutamine had no effect on SGIV infection, indicating that glucose was required for SGIV replication. Consistently, pharmacological inhibition of glycolysis dramatically reduced the protein synthesis of SGIV major capsid protein (MCP) and infectious virion production, and promotion of glycolysis significantly increased SGIV infection. Furthermore, knockdown of HK2, PDHX or GLUT1 by siRNA decreased the transcription and protein synthesis of SGIV MCP and suppressed viral replication, indicating that those enzymes exerted essential roles in SGIV replication. In addition, inhibition of mTOR activity in SGIV-infected cells effectively reduced the expression of glycolysis key enzymes, including HK2, PDHX, GLUT1 and GLUT2, and finally inhibited SGIV replication, suggesting that mTOR was involved in SGIV-induced glycolysis. Thus, our results not only provided new insights into the mechanism of how SGIV infection affects host cell glycolysis, but also contributed to further understanding of the iridovirus pathogenesis.